2022
DOI: 10.1021/acsapm.2c00467
|View full text |Cite
|
Sign up to set email alerts
|

PI-LAGP Separator─Construction, Battery Application Performance, and Chemical Valence Changes of Germanium

Abstract: We successfully prepared a porous polyimide film (PIBPDA–ODA) with a three-dimensional network structure using an optimized amount of pore-forming agents and a nonsolvent-induced phase separation method. Then, the nanoparticles of an inorganic ion conductor Li1.5Al0.5Ge1.5(PO4)3 (LAGP) were filled into the pore of the PIBPDA–ODA to form a PI–LAGP composite film with an ionic conductivity of 1.42 mS·cm–1 and a lithium-ion transference number of 0.87 (at room temperature). A NCM811||Li battery assembled with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Note that a recent experimental study showed that the commercial cellulose-based separators show similar swelling and weakening behavior as polyolefins; we expect our model could also apply to those materials. Furthermore, much work in recent years has been focused on developing new battery separator materials, while only a few of them assess the new materials for swelling and softening in the presence of electrolyte solvents. Our model can help make such an assessment with minimal experimental effort.…”
Section: Discussionmentioning
confidence: 99%
“…Note that a recent experimental study showed that the commercial cellulose-based separators show similar swelling and weakening behavior as polyolefins; we expect our model could also apply to those materials. Furthermore, much work in recent years has been focused on developing new battery separator materials, while only a few of them assess the new materials for swelling and softening in the presence of electrolyte solvents. Our model can help make such an assessment with minimal experimental effort.…”
Section: Discussionmentioning
confidence: 99%